PERBEDAAAN PENURUNAN MASA BIOFILM Streptococcus mutans ANTARA PEMBERIAN FRAKSI N-HEKSANA DAN ETIL ASETAT EKSTRAK ETANOL BAWANG PUTIH SIUNG TUNGGGAL (Allium sativum L.) - Ratna Indriyanti; Faizal Hasan; Meirina Gartika (Odonto : Dental Journal, 2019)
Background: Garlic (Allium sativum L) is one of the most important Allium species consumed worldwide and has been used for decades as a cure for various diseases. The aim of this research was to compare the efficacy of single-clove garlic’s n-hexane and ethyl acetate fractions in inhibiting the growth of Streptococcus mutans biofilmMethod: This was a true experimental research. The biofilm mass was determined by absorbance value at 590 nm wavelength with ELISA reader in a microplate using safranin. Data was analyzed using ANOVA followed by post hoc analysis with ρ value <0.05.Result: The result showed that average decrease of biofilm mass after 1-30 minutes of ethyl acetate fraction administration was 33.4 ± 8.03 mg/mL, n-hexane 23.6 ± 0.97 mg/mL and chlorhexidine 35.5 ± 0.98 mg/mL. The average decrease of biofilm mass after 30-60 minutes of ethyl acetate fraction administration was 11.94 ± 7.44 mg/mL, n-hexane 43.87 ± 41.6 mg/mL and chlorhexidine 16.35 ± 4.6 mg/ mL. Statistic analysis showed that there was a notable difference in the decrease of Streptococcus mutans biofilm mass (ρ value= 0.00). Conclusion: The conclusion of this research was that administrating either n-hexane or ethyl acetate fractions of a single-clove garlic has the ability to decreaseS. mutans biofilm mass.